Illocution as a Multidimensional Communicative Category: Integrative Analysis of Speech Act Theory, Cognitive Pragmatics, Interactional Discourse, and Social Semiotics (KONFERENSIYA, 2025)
This extended analytical article explores illocution as a central communicativemechanism by synthesizing classical speech act theory, cognitive-inferentialpragmatics, interactional linguistics, and social semiotics. Drawing on V.N.Vasilina’s foundational research alongside the work of Austin, Searle, Grice,Goffman, Brown & Levinson, Heritage, van Dijk, Weigand, Bhatia, Mey, Halliday,Tomasello, Clark, Sperber & Wilson, and Karaulov, the study argues that illocution isnot a simple linguistic feature but a multilayered semiotic action embedded inintention, cognition, social norms, and discourse organization. The analysisdemonstrates that illocution emerges from the interaction between linguistic form,mental states, inferential reasoning, cultural expectations, and interactionalsequencing. The article concludes that illocution is a dynamic, negotiable, culturallysituated phenomenon that requires a comprehensive interdisciplinary perspective